New immigrants. An incentive for intercultural education?. Issue 3 (3rd July 2019) - Leeman, Yvonne; van Koeven, Erna
ABSTRACT: This study was inspired by an inclusive intercultural perspective on education, and developed empirical knowledge concerning the intercultural professional development of in-service teachers. The study was conducted during the first year of a newly-designed master's programme that focused on "education for refugees". In the Netherlands master's programmes in education qualify in-service teachers to contribute to school development, together with giving them a specialisation in a specific topic. The findings were based on the teachers' written work, and interviews with the teacher educators. They show that the intercultural professional identity of the teachers was developed by a combination of pedagogical approaches. These include the following: new knowledge from an inclusive intercultural perspective, critical socio-cultural self-examination, real encounters with newly-arrived refugees, and a reflective, intervention-based approach to professional learning and curriculum renewal. The intervention-based approach turned out to be the most important for the teachers' agency in intercultural school development. The challenges experienced concern mono-cultural practices in mainstream education for refugees, together with the dominance of an instrumentalist approach to teaching and learning.